The Effectiveness of the Multiliteracy Integrative Learning (MULGRANING) Model on Students' Reading Skills in Indonesian Language Learning - Indriyani, Vivi; Zakarya, Zaiton (Language Pedagogy Study Program, Faculty of Languages and Arts, Universitas Negeri Padang, Indonesia, 2025)
Good reading ability is a fundamental skill in learning Indonesian, especially in understanding, analyzing, and evaluating scientific texts critically. However, various studies show that many students still have difficulty in understanding the structure, meaning, and content of the text in depth, which has an impact on their low analytical skills. Therefore, an innovative learning model is needed that can improve reading skills effectively, one of which is through the application of Multiliteracy Integrative Learning (MULGRANING). Using a quantitative approach with a quasi-experimental method, this study applied a one-group pre-test post-test design to 34 grade XI students at SMAN 2 Padang. The experimental class using the MULGRANING model was implemented with eight steps, namely experiencing, conceptualizing, analyzing, producing & creating, networking, applying, comparing, and synthesizing. While the control class was implemented with conventional learning. Data were collected through descriptive tests and analyzed using the Wilcoxon Signed-Rank Test in SPSS. The results showed that all students experienced an increase in reading scores after the MULGRANING model was applied. No students were found to have decreased scores or had the same pre-test and post-test scores. The Z value of -5.103 with a p-value of 0.000 indicates that this model is significantly effective in improving reading skills. These findings indicate that the MULGRANING model can be an innovative learning alternative to help students understand, analyze, and evaluate texts better. Therefore, the application of this model is recommended more widely to improve the quality of reading learning in secondary schools.